Potential distribution prediction of Deyeuxia angustifolia in the Tumen River Basin and analysis of major impact factors - Zong, Jin; Cao, Guanglan; Jin, Xuemei; Jin, Ri; Zhu, Weihong (Frontiers in Environmental Science, 2022)
Deyeuxia angustifolia plays an important indicator role and has ecological value for the changes and functions of wetlands. Although wetland conservation measures have been implemented in recent years, the distribution area of Deyeuxia angustifolia has decreased due to climate change and anthropogenic activities. Therefore, we used the MaxEnt model and Geographic Information System(GIS) to model the suitable habitat for Deyeuxia angustifolia, simulated changes in the suitable habitat, and applied Jackknife to assess environmental variables. The Jackknife test showed that the slope direction, solar radiation in September, and total nitrogen were the dominant environmental factors affecting the potential distribution of Deyeuxia angustifolia. Compared to the current distribution, the total area of highly suitable and moderately suitable land for Deyeuxia angustifolia will decrease in the 2050s and 2070s under both representative concentration pathways (RCPs). However, the total area of unsuitable land will increase. The models suggest that topography and soil are the main environmental factors influencing the distribution of Deyeuxia angustifolia, shifting the centroid of its suitable area and the direction of wetland degradation to the northeast. Our study of the projected potential distribution of Deyeuxia angustifolia under future climate change could provide important information for its conservation, management, sustainable use, and early warning.